Characteristics of wet and dry spells in the West African monsoon system. (21st February 2017) - Froidurot, Stéphanie; Diedhiou, Arona
Abstract: Using 17 years (1998–2014) of daily TRMM 3B42 rainfall data, we provide a climatological characterization of wet and dry spells in West Africa, which should serve to assess the ability of climate model to simulate these high impact events. The study focuses on four subregions (Western and Central Sahel, Sudanian zone and Guinea Coast). Defining wet (dry) spells as sequences of consecutive days with precipitation higher (lower) than 1 mm, we describe the space‐time variability of wet and dry spell occurrence. This climatology stresses the influence of the relief on the number and duration of these spells. The spatio‐temporal variability of the wet and dry spells also appears to be closely related to the spatio‐temporal variability of the West African monsoon. The number of wet spells of all durations and of 2–3 day dry spells have similar features with a maximum occurrence during the local rainy seasons and a spatial pattern similar to the mean annual rainfall with a north–south gradient. In contrast, dry spells lasting more than four days show some singularities such as a low occurrence over the Sahelian band or high occurrence along the Guinea Coast mainly from Ivory Coast to Benin. Moreover, the seasonal cycle of these longer dry spells presents higher occurrences at the beginning and the end of the rainy seasons.